The deductibility of Sarbanes-Oxley costs incurred by Australasian companies. Issue 1 (1st July 2014) - Harrison, Julie; Keating, Mark
Abstract : Purpose: – This paper aims to examine the nature of Sarbanes-Oxley (SOX) costs incurred by subsidiaries of USA parent companies, and considers whether any value flows to non-USA subsidiaries. Deductibility is analysed under both the general deductibility provisions and the transfer pricing regimes of Australia and New Zealand (NZ). Reference is also made to the Organisation for Economic Cooperation and Development (OECD) transfer pricing guidelines and the US transfer pricing regulations. Australasian and New Zealand subsidiaries of US parent companies frequently incur costs related to their parent's regulatory reporting requirements under the Sarbanes-Oxley Act of 2002. Tax authorities, generally, view these costs as "shareholder activities", i.e. activities performed for the benefit of the parent only. As such, they are considered non-deductible to the subsidiaries of USA parents because an independent party dealing at arm's length would not pay to receive similar services. We consider circumstances in which some costs may be deductible. Design/methodology/approach: – Legal analysis. Findings: – We conclude that there can be circumstances where these so-called shareholder activities do provide value to subsidiaries and, accordingly, may (or should) be deductible in the local jurisdiction. Research limitations/implications: – This analysis is limited to a consideration of Australian, NZ, OECD and US sources. Practical implications: – This paper provides an analysis of the deductibility of a type of expenditure commonly encountered by subsidiaries of US parent companies. Originality/value: – Limited research is available that deals with this issue. In most cases, only general statements on deductibility of similar types of expenditure are available to taxpayers.